«Squinternati e crassosi romanzi»: per un’indagine su Gadda lettore di Céline - Basile, Francesco (L’ospite ingrato, 2024)
The essay offers a comparative analysis of two textual loci from La cognizione del dolore and Voyage au bout de la nuit, aiming to shed light on the possible presence of Voyage among the many sources Gadda utilized during the composition of La cognizione del dolore. The first part of the essay presents a thematic comparison of the two passages, suggesting that the segment in La cognizione del dolore might have been inspired by the reading of the Célinian passage. Subsequently, the study focuses on certain linguistic aspects of the two excerpts, formulating the hypothesis that a neologism present in the Gaddian text could be considered a linguistic calque derived from French, and specifically from Céline’s novel.